Born-infeld corrections to the entropy function of heterotic black holes - Chandrasekhar, B. [UNESP] (FapUNIFESP (SciELO), 2007)
We use the black hole entropy function to study the effect of Born-Infeld terms on the entropy of extremal black holes in heterotic string theory in four dimensions. We find, that after adding a set of higher curvature terms to the effective action, attractor mechanism, works and Born-Infeld terms contribute to the stretching of near horizon geometry. In the α′ → 0 limit, the solutions of attractor equations for moduli, fields and the resulting entropy, are in conformity with the ones for standard two charge black holes.
Keywords: Black hole entropy; Born-infeld terms; Extremal black holes; String theory